2015
DOI: 10.1128/genomea.01514-14
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Newcastle Disease Virus Isolated from a Rock Dove (Columba livia) in the Russian Federation

Abstract: We report here the complete genome sequence of a Newcastle disease virus (NDV) isolate, NDV/Altai/pigeon/770/2011, isolated from a rock dove in the Russian Federation. On the basis of phylogenetic analysis, this strain was clustered into genotype VIb class II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…The selected strains represented different NDV pathotypes: NDV/Yakutiya/mallard/852/2011 (852)–mesogenic pathotype with the typical avirulent type F-gene sequence [ 27 ], NDV/Altai/pigeon/770/2011 (770)–mesogenic pathotype with the typical virulent type F-gene sequence [ 28 ] and Adygea/duck/12/2008 (AD)–velogenic pathotype [ 29 ]. There were no changes in viability of suspended PBMCs even after 4 days of infection with different NDV strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected strains represented different NDV pathotypes: NDV/Yakutiya/mallard/852/2011 (852)–mesogenic pathotype with the typical avirulent type F-gene sequence [ 27 ], NDV/Altai/pigeon/770/2011 (770)–mesogenic pathotype with the typical virulent type F-gene sequence [ 28 ] and Adygea/duck/12/2008 (AD)–velogenic pathotype [ 29 ]. There were no changes in viability of suspended PBMCs even after 4 days of infection with different NDV strains.…”
Section: Resultsmentioning
confidence: 99%
“…Here we investigate the oncolytic properties of 44 wild-type NDV isolates obtained from migratory birds in Russia in Western Siberia and the Far East from 2008 to 2014. Most of the viruses were isolated from Anseriformes and proved avirulent and lentogenic except one velogenic and several mesogenic isolates including NDV/Altai/pigeon/770/2011 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sub-genotype VIf viruses have been repeatedly recovered from pigeons in the United States during 1984(Hines et al, 2012Benson et al, 2015). Viruses from sub-genotype VIg have been isolated from pigeons and a dove in Nigeria, Russia, and Ukraine during -2011(Van Borm et al, 2012Pchelkina et al, 2013;Yurchenko et al, 2015;Benson et al, 2015). The earliest confirmed subtype VIh isolate was recovered from a pigeon in Argentina in 1997 (Benson et al, 2015) There is a group of viruses that has only been found in chickens in Ethiopia (during 2011-2012) (de Almeida et al, 2013;Mulisa et al, 2014) and is highly related to viruses of genotype VI.…”
Section: Class II Genotype Vimentioning
confidence: 99%
“…Патотип определяется после выделения вируса с помощью стандартных тестов патогенности -среднего времени смерти (MDT) и интрацеребрального индекса патогенности (ICPI). Исследования по изучению патогенных свойств выделенных изолятов в тестах MDT и ICPI показали, что все изоляты ВБН являются не патогенными (MDT>100 ч, ICPI=0,0), за исключением двух штаммов -NDV/Altai/pigeon/770/2011 (GenBank accession no.KJ920204) [12] и NDV/Yakutiya/mallard/852/2011 (GenBank accession no.KJ920203) [13] (табл.3). ШтаммNDV/Altai/pigeon/770/2011 в разведении 10 -7 привел к 100% летальности 10-ти дневные РКЭ через 76 часов после инфицирования, однако индекс ICPIсоставил 0,68.…”
Section: материалы и методы исследованияunclassified